If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 2b + -3 Reorder the terms: 7 = -3 + 2b Solving 7 = -3 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 7 + -2b = -3 + 2b + -2b Combine like terms: 2b + -2b = 0 7 + -2b = -3 + 0 7 + -2b = -3 Add '-7' to each side of the equation. 7 + -7 + -2b = -3 + -7 Combine like terms: 7 + -7 = 0 0 + -2b = -3 + -7 -2b = -3 + -7 Combine like terms: -3 + -7 = -10 -2b = -10 Divide each side by '-2'. b = 5 Simplifying b = 5
| 4x+11=41 | | 0.06x+0.09(15-x)=0.07 | | 3x-4=9-2x | | 2x=-4x-6 | | 6(2-7r)=-27 | | 15-3s=3 | | 91=4u+15 | | 13x=145 | | 9b-10-8b=-13 | | 16-7s=-9s-20 | | 2x(4x+1)=7 | | 10x-3+3x+5=186 | | 27-9h=-4(5h-2) | | 11x=-9 | | 16-7s=9s-20 | | f(x)=x-4/x(x-4) | | 8=8(w-5)+4w | | 2/5x-16=-6 | | 0.675*t^2-2*t+2=0 | | 2(2k+1)x+5(2k+1)y-3k-1=0 | | 1/3(2x-3)3/4(2-4x) | | 20=3(y+4)-7y | | 6x+4=7x-19 | | 1+4u-16=3u-5 | | 2/5x-16= | | 3(v-2)-5v=2 | | x^2-8x^2=9 | | 6(9k-7)=-30 | | 0.675*t^2-2*t=-2 | | 4-(x-5x)=8-2x | | 3a-4=k | | 20x+200=400 |